Mechanisms of Vascular Remodeling in Hypertension - Humphrey, Jay D (American journal of hypertension, 2021)
Hypertension is both a cause and a consequence of central artery stiffening, which in turn is an initiator and indicator of myriad disease conditions and thus all-cause mortality. Such stiffening results from a remodeling of the arterial wall that is driven by mechanical stimuli and mediated by inflammatory signals, which together lead to differential gene expression and concomitant changes in extracellular matrix composition and organization. This review focuses on biomechanical mechanisms by which central arteries remodel in hypertension within the context of homeostasis-what promotes it, what prevents it. It is suggested that the vasoactive capacity of the wall and inflammatory burden strongly influence the ability of homeostatic mechanisms to adapt the arterial wall to high blood pressure or not. Maladaptation, often reflected by inflammation-driven adventitial fibrosis, not just excessive intimal-medial thickening, significantly diminishes central artery function and disturbs hemodynamics, ultimately compromising end organ perfusion and thus driving the associated morbidity and mortality. It is thus suggested that there is a need for increased attention to controlling both smooth muscle phenotype and inflammation in hypertensive remodeling of central arteries, with future studies of the often adaptive response of medium-sized muscular arteries promising to provide additional guidance.